Revisiting the social cost of carbon after INDC implementation in Malaysia: 2050 - Sarkar M.S.K.; Al-Amin A.Q.; Filho W.L. (Springer Verlag, 2023)
carbon emission; climate change; emission control; environmental economics; pollution tax; social participation; willingness to pay; Malaysia; carbon; carbon dioxide; carbon sequestration; climate change; economics; environmental policy; environmental protection; Malaysia; socioeconomics; Carbon; Carbon Dioxide; Carbon Sequestration; Climate Change; Conservation of Natural Resources; Environmental Policy; Malaysia; Socioeconomic Factors